(untitled) (Journal of Libya for geographical studies, 2021)
This study dealt with analyzing wind energy sources in the central region of Libya, in terms of their concept, importance, and possibility of investing in the production of electric energy, based on the problem and hypothesis of the research and ultimately reaching the environmental capabilities available to invest these sources, represented by wind energy in the study area, from During the study of the climatic data for three main stations in the study area, namely the stations of Sirte, Hun and Misurata, it was revealed through the study that the wind speed reached annual averages of 3.8, 3.9, and 4.64 m / s respectively. It is possible to produce electrical energy based on these averages with a power of 35.39, 38.26 and 66.1 watt / m2 respectively, and study the quantities that can be produced from electrical energy in the event that wind energy is exploited in the region, as well as the production of electric energy in Libya by fossil fuels and the amount of Pollution from carbon dioxide emissions, and the study concluded with a set of conclusions and recommendations.